1989
DOI: 10.1073/pnas.86.12.4407
|View full text |Cite
|
Sign up to set email alerts
|

Methionine synthesis in Escherichia coli: effect of the MetR protein on metE and metH expression.

Abstract: Studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…In E. coli the MetR protein activates expression of the metH and metE genes and probably metA, all of which are involved in methionine synthesis. Also, metR has been shown to downregulate its own transcription and to be repressed by MetJ (9,24). The methionine synthase genes metH (PA1843) and metE (PA1927) are present in P. aeruginosa and are 79% and 74% similar to their E. coli counterparts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli the MetR protein activates expression of the metH and metE genes and probably metA, all of which are involved in methionine synthesis. Also, metR has been shown to downregulate its own transcription and to be repressed by MetJ (9,24). The methionine synthase genes metH (PA1843) and metE (PA1927) are present in P. aeruginosa and are 79% and 74% similar to their E. coli counterparts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that under the growth conditions tested in the present study the repressive effect of MetJ-SAM on metE transcription outweighs the inducing effect of MetR-Hcy. Indeed, an in vitro study of metE transcription has shown that MetR-Hcy fails to induce metE in the presence of MetJ-SAM (Cai et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The metA gene, as well as all of the other methionine biosynthetic genes except metH, is negatively regulated by the MetJ repressor, with S-adenosylmethionine acting as a corepressor. In addition to MetJ-mediated repression, at least two genes, the metE and metH genes, are activated by MetR, a DNA-binding protein (4,28). Although homocysteine is required for the MetR-mediated activation of the metE gene, homocysteine plays an inhibitory role in the MetR-mediated activation of the metH gene (5,29).…”
mentioning
confidence: 99%